Lung clearance index short-term variability in cystic fibrosis: a pre-post pulmonary exacerbation study - Matteo De Marchis; Enza Montemitro; Alessandra Boni; Alessandra Federici; Daniele Di Giovanni; Luca Cristiani; Renato Cutrera; Alessandro G. Fiocchi (BMC, 2024)
Abstract Background Multiple Breath washout (MBW) represents an important tool to detect early a possible pulmonary exacerbation especially in Cystic Fibrosis (CF) disease. Lung clearance index (LCI) is the most commonly reported multiple breath washout (MBW) index and in the last years was used as management measure for evaluation. Our aim was to analyze clinical utility of LCI index variability in pulmonary exacerbation in CF after intravenous (IV) antibiotic therapy. Methods A single-center study was conducted at CF Unit of Bambino Gesù Children's Hospital among hospitalized > 3 years patients for pulmonary exacerbations and treated with antibiotic IV treatment for 14 days. MBW and spirometry were evaluated within 72 h of admission to hospital and at the end of hospitalization. Descriptive analysis was conducted and correlations between quantitative variables were investigated. Results Fifty-seven patients (M22/F35) with an average age 18.56 (± 8.54) years were enrolled. LCI2.5 was significantly reduced at the end of antibiotic treatment in both pediatric and adult populations with an average reduction of -6,99%; 37/57 patients denoted an improvement, 20/57 are stable or worsened in LCI2.5 values and 4/57 (7.02%) had a significant deterioration (> 15%) at end of treatment. On the contrary a significative elevation of FEV1 and FVC were found, respectively of + 7,30% and of + 5,46%. A positive good correlection among LCI 2.5 and Scond (rho = + 0,615, p = 0.000) and LCI 2.5 and Sacin (rho = + 0,649, p = 0.000) and a negative strong correlation between FEV1 and LCI 2.5 were found in post treatment period. A similar modification of LCI 2.5 and FEV1 was noticed in both adult and pediatric population. Conclusions LCI may have a role in the routine clinical care of both adult and pediatric CF patients as a good tool to assess response to IV antibiotic end-therapy in the same way as FEV1.